Gastrostomy Placement Rates in Infants with Pierre Robin Sequence: A Comparison of Tongue-Lip Adhesion and Mandibular Distraction Osteogenesis. Issue 1 (January 2017) - Susarla, Srinivas M.; Mundinger, Gerhard S.; Chang, Christopher C.; Swanson, Edward W.; Lough, Denver; Rottgers, S. Alex; Redett, Richard J.; Kumar, Anand R.
Abstract : Background: This study was conducted to compare the gastrostomy rates in infants with Pierre Robin sequence treated with tongue-lip adhesion or mandibular distraction osteogenesis. Methods: This was a retrospective study of symptomatic plastic and reconstructive surgery patients treated over an 8-year period. The primary predictor variable was surgical intervention (tongue-lip adhesion or distraction osteogenesis). Secondary predictor variables were categorized as demographic and clinical factors. The primary outcome was the need for gastrostomy tube placement. Secondary outcomes were complication rates, costs, and length of stay. Results: Thirty-one tongue-lip adhesion and 30 distraction osteogenesis patients were included in the study. The groups were statistically comparable with regard to demographic and clinical factors ( p > 0.18). Gastrostomy rates were higher in patients who underwent tongue-lip adhesion (48 percent) versus those who underwent distraction osteogenesis (16.7 percent; p = 0.008). In an adjusted model, subjects undergoing tongue-lip adhesion were more likely to require gastrostomy tube for nutritional support (OR, 6.5; 95 percent CI, 1.7 to 25.2; p = 0.007). There were two major complications in the tongue-lip adhesion group and none in the distraction osteogenesis group. There were three minor complications in the tongue-lip adhesion group and five in the distraction osteogenesis group. Total operating room costs were higher for distraction osteogenesis ( p = 0.05), and total hospital costs and length of stay were higher for tongue-lip adhesion ( p < 0.05). Conclusions: Among infants with symptomatic Pierre Robin sequence, treatment by distraction osteogenesis is associated with a lower risk for gastrostomy placement for nutritional support. Hospital costs are higher for tongue-lip adhesion. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.